Analisis Penggunaan Siskeudes dalam Pengelolaan Dana Desa - Desy Nur Pratiwi; Yuwita Ariessa Pravasanti (ITB AAS INDONESIA, 2020)
The government provides village funds to improve the welfare of rural communities and equitable development. The purpose of this study was to examine internal and external factors that influence the use of Siskeudes. This study uses primary data in the form of questionnaires and distributed to village fund managers in eight districts in Sukoharjo Regency. The sample collection technique in this study uses convenience sampling method and the total number of samples collected is 32 villages. Hypothesis testing uses multiple linear regression. Partial test results indicate that the variable usefulness (perceived usefulness) and interest in using technology (behavioral intention to use) affect the use of Siskeudes. Simultaneous test results show that the perceived usefulness (perceived usefulness) and interest in using technology (behavioral intention to use) together affect the use of Siskeudes. Keywords: behavioral intention to use, perceived usefulness and Siskeudes